Superior thermal dissipation through natural convection in a passive cooling system using multidirectional tapered fin heat sinks (MTFHS) - Razali, Siti Nuraisyah; Ibrahim, Adnan; Fazlizan, Ahmad; Al-Aasam, Anwer B.; Rahmat, Muhammad Aqil Afham; Ishak, Muhammad Amir Aziat (Center of Biomass & Renewable Energy (CBIORE), 2025)
The increasing prominence of photovoltaic modules as a cornerstone of sustainable energy systems is well-established. Nevertheless, the deleterious impact of thermal dissipation, often resulting in efficiency losses of 10-15%, remains a significant challenge. Many researches were exploring new cooling techniques to improve the efficiency of solar panels. One promising approach is the Multidirectional Tapered Fin Heat Sink (MTFHS). This innovative design can capture wind from multiple directions, making it more effective outdoors. This study aims to investigate the MTFHS for photovoltaic module cooling. A comprehensive numerical model was developed using COMSOL software simulations to investigate the thermal behavior of photovoltaic modules equipped with multidirectional tapered fins. The model was employed to simulate heat transfer under various solar irradiance levels from 400 W/m2 to 1000 W/m2 while maintaining a constant 30 ℃ ambient temperature and 1 m/s wind speed to isolate the impact of solar radiation. Additionally, the direction of incoming airflow was systematically varied from 0° to 90° in 18° increments to analyze its influence. The model considered key multidirectional tapered fin design parameters like fin spacing, number of fins, and fin height. Real-world testing further validated the model's predictions. The findings demonstrate that multidirectional tapered fins significantly reduce PV module temperature, achieving a remarkable 8.61% reduction compared to the bare and conventional rectangular fins. The maximum temperature reached with MTFHS was 56.73 ℃. Furthermore, multidirectional tapered fins consistently outperformed other configurations across various wind orientations, achieving temperature reductions of over 10 %. These findings highlight the exceptional effectiveness of multidirectional tapered fins in outdoor environments, especially where wind direction is unpredictable. A correlation analysis revealed excellent agreement (93-96 %) between model and experimental results, further validating the efficacy of the multidirectional tapered fin design.